The changing faces of global cities and firms: a new perspective on firms’ location strategy - Asakawa, Kazuhiro; Clegg, Jeremy (Journal of International Business Studies, 2024)
Recognizing the dearth of attention afforded to global cities in the international business and management journals, Goerzen et al. (J Int Bus Stud 44(5):427–450, 2013) chanced their hand at becoming pioneers. Their gamble paid off. Taking geographic scale down to the city level, questioning why multinationals choose to locate subsidiaries inside or outside of global cities, they jump-started their own conversation, sugaring the pill with the IB staple—liability of foreignness. So well was their inquiry crafted and executed that their insights into the way global connectedness attracts investment into these cities remains instructive. Since then, global cities and firms have undergone a transition. We visualize increasingly multifaceted cities interacting with firms accelerating towards adopting an “ecosystem approach”—characterized by extensive non-equity collaborations and partnerships. We explain why investigation à la Goerzen et al. (J Int Bus Stud 44(5):427–450, 2013) today must grasp multinationals’ diverse relationships to revivify theoretical insights from economic geography for a world of tensions heightened by geopolitics, but above all grappling with the sustainability agenda. We conclude that within an ecosystem of feedback effects, multinationals’ agency can be part of the solution. To deliver, IB must harness emerging novel geographic—“big”—data and techniques to match, in the spirit of the imaginative fusion a decade earlier.